The End of Islands: Drawing Insight from Revelation to Respond to Prisoner Radicalization and Apocalyptically-Oriented Terrorism - Trinka, Eric ca. 20./21. Jh. (Religions, 2019)
This paper is an exploratory exercise in practical theology and interfaith engagement that probes the conceptual frameworks of insularity (Islandness) and incarceration in Revelation in order to address the related problems of prisoner radicalization and apocalyptically-oriented terrorism. It offers an experimental reading of Revelation performed through the lenses of island studies, criminology, and research on prisoner radicalization. While inmates may adopt a range of religious dispositions, Islam is the fastest-growing religion in U.S. prisons. Moreover, even though Islam is not inherently violent nor are Muslims more predisposed to radical behaviors than other religious groups, some forms of prison Islam promote brutal apocalyptic worldviews and incite adherents to violence. This paper examines the place Revelation maintains in Islamic apocalyptic thought and asks how Revelation can assist in the fight against radicalization among an increasingly Muslim inmate population. Islands, prisons, and prisoners share a robust set of real and metaphorical relationships. The islanded nature of John's experience provides a valuable point of access for incarcerated readers who find themselves in similarly marginalized social locations where radical readings are more likely to occur. Reading the insular and carceral elements of Revelation in tandem with these bodies of research is instructive for cultivating constructive responses to the present set of problems. It is argued that while Revelation can be a potential source of violent ideologies, it also offers its own internal checks against violent enactments. John's vision culminates in the end of islands (Rev 21:1). The overarching goal of this essay is to ask how we might point readers in physically and ideologically insular environments toward constructive interpretations of apocalyptica in order to stem the persistent problem of violent radicalization.